Determination of XLR-11 Metabolites in Urine by Ultrahigh-performance Liquid Chromatography-tandem Mass Spectrometry - (:unkn) unknown (PLEIADES PUBLISHING INC, 2020)
In recent years, the use of cannabinoids has gained increasing attention both in the scientific community and regulatory/government agencies. Likewise, the use of synthetic cannabinoids is also increasing. In view of their growing need and popularity, specific and robust methods are required to detect these drugs. One such example is XLR-11 (5-fluoro-UR-144), a drug that acts as a potent agonist for cannabinoid receptors CB1 and CB2 (with EC50 values of 98 and 83 nM, respectively), excessively used nowadays. In this study, we developed a simple, efficient, precise, and sensitive ultrahigh-performance liquid chromatography-tandem mass spectrometry method to simultaneously determine metabolites of XLR-11 N-(4-hydroxypentyl) and XLR-11 N-(4-pentenyl) analog. This method was validated in terms of selectivity and linearity which was in the range of 6-60 ng/mL for XLR-11 N-(4-hydroxypentyl) and between 51-515 ng/mL for XLR-11 N-(4-pentenyl) analog, intra-assay and inter-assay accuracy, and precision (coefficient of variation <15%). Lower limits of quantitation were 6 and 51 ng/mL for XLR-11 N-(4-hydroxypentyl) and XLR-11 N-(4-pentenyl) analog, respectively. Matrix effects and stability were also assessed. Based on the results obtained, it can be seen that this method is efficient, precise, and highly reliable for the determination of XLR-11 metabolites in the urine samples.
Keywords: XLR-11 metabolites; ultrahigh-performance liquid chromatography-tandem mass spectrometry; urine samples; method development and validation; SYNTHETIC CANNABINOIDS; PHARMACOLOGY